2008
DOI: 10.3354/ab00037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification on the immune response of the blue mussel Mytilus edulis

Abstract: The effects of medium term (32 d) hypercapnia on the immune response of Mytilus edulis were investigated in mussels exposed to acidified (using CO 2 ) sea water (pH 7.7, 7.5 or 6.7; control: pH 7.8). Levels of phagocytosis increased significantly during the exposure period, suggesting an immune response induced by the experimental set-up. However, this induced stress response was suppressed when mussels were exposed to acidified sea water. Acidified sea water did not have any significant effects on other immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
154
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(163 citation statements)
references
References 33 publications
3
154
2
4
Order By: Relevance
“…Nevertheless, OA exposure did not affect the apoptosis of hematopoietic tissue cell in the crustacean N. norvegicus [21]. Above all, OA had an impact on immune response of the Pacific oyster, which might be attributed to less energy spent on immune response [18].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Nevertheless, OA exposure did not affect the apoptosis of hematopoietic tissue cell in the crustacean N. norvegicus [21]. Above all, OA had an impact on immune response of the Pacific oyster, which might be attributed to less energy spent on immune response [18].…”
Section: Discussionmentioning
confidence: 85%
“…For example, OA was found to impact survival, development, physiology and growth of many marine mollusks [32]. Furthermore, OA exposure can also disturb the energy metabolism and regulation which might affect immune function in bivalves [14,18]. Recently, it has been found that OA stress has the potential to promote pathogen development and survival, disease transmission and host susceptibility [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this importance only a handful of studies have, to date, investigated the impact of OA on the immune system of a marine organism. The first study undertaken, carried out by Bibby et al (2008), exposed the blue mussel, Mytilus edulis, to reduced seawater pH for 32 days, measuring a number of key immune responses over the course of the experiment. Mussels maintained in reduced pH seawater (7.7, 7.5 or 6.7) displayed reduced phagocytic activity, compared with controls maintained at pH 7.8, after the 32 day exposure.…”
Section: Introductionmentioning
confidence: 99%